2000
DOI: 10.1053/euhj.1999.2012
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and lack of social integration in relation to prognosis of CHD in middle-aged women. The Stockholm Female Coronary Risk Study

Abstract: The presence of two or more depressive symptoms and lack of social integration independently predicted recurrent cardiac events in women with coronary heart disease. Women who were free of both these risk factors, had the best prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(102 citation statements)
references
References 47 publications
4
95
1
2
Order By: Relevance
“…Similarly, depression and depressive symptoms have been related to CVD and cognitive performance. [31][32][33][34] However, the use of depression as an explanatory concept for the gender-specific results of the present study is weakened by the fact that, among the Framingham Offspring, men exhibited lower levels of depressed mood than did women, and neither…”
Section: 29mentioning
confidence: 48%
“…Similarly, depression and depressive symptoms have been related to CVD and cognitive performance. [31][32][33][34] However, the use of depression as an explanatory concept for the gender-specific results of the present study is weakened by the fact that, among the Framingham Offspring, men exhibited lower levels of depressed mood than did women, and neither…”
Section: 29mentioning
confidence: 48%
“…Kaplan et al, 1994;Orth-Gomer, Rosengren, & Wilhelmsen, 1993;Pennix et al, 1997;Seeman et al, 1993;Vogt, Mullooly, Ernst, Pope, & Hollis, 1992). Social isolation is particularly unhealthy in patients with preexisting CHD (Angerer et al, 2000;Berkman, Leo-Summers, & Horwitz, 1992;Case, Moss, Case, McDermott, & Eberly, 1992;Gorkin et al, 1993;Horsten et al, 2000;Krumholz et al, 1998;Welin, Lappas, & Wilhelmsen, 2000;R. B. Williams et al, 1992;Woloshin et al, 1997), although different indicators of support and isolation sometimes produce inconsistent effects (Irvine et al, 1999).…”
Section: Social Isolation and Conflictmentioning
confidence: 99%
“…The following values were adopted to define the control of risk factors: systolic blood pressure < 140 mmHg and diastolic blood pressure < 90 mmHg (in diabetic patients, these values were decreased to 130 and 80 mmHg, respectively); fasting glycemia ≤ 126 mg/dl; LDL-cholesterol ≤ 100 mg/dl; BMI < 25 kg/m²; and triglycerides ≤ 150 mg/dl 13,16,17 .…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Additionally, patients with established coronary artery disease (CAD) present QoL impairment and high levels of stress, caused by the disease itself, physical limitation and risk of death, closing a vicious circle that intensifies the disease progression [1][2][3][4] . It is believed that, in addition to disease severity, the association of comorbidities, such as diabetes mellitus (DM), arterial hypertension (AH) and obesity, frequently Another study 13 showed that women older than 65 years with symptoms of depression presented an unfavorable clinical evolution, with worse prognosis, six months after a cardiovascular event.…”
Section: Introductionmentioning
confidence: 99%